If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 5 = x Reorder the terms: 5 + 3n = x Solving 5 + 3n = x Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3n = -5 + x Combine like terms: 5 + -5 = 0 0 + 3n = -5 + x 3n = -5 + x Divide each side by '3'. n = -1.666666667 + 0.3333333333x Simplifying n = -1.666666667 + 0.3333333333x
| 16x^2+1=3x | | 16x^2-3x+1=0 | | 2u^2-10u=0 | | 30-15b=2+2b | | (v+3)(v-12)=0 | | 96=4w+2w^2 | | 4a^4-8a^3=0 | | x^2+3x=8 | | 100=3w^2+13w | | -10-2x=6x-2 | | 3s-1=-8 | | 3/8=z/5 | | 6x-1=3x+47 | | 4=-3a+2 | | 3x-28= | | 1-5m=-3 | | y^2-5y+36=y+1 | | y+7=15y | | 8x^3-36x^2+48x-16=0 | | 5.7x^2-3.2x=2 | | 6x-(3x+7)=17 | | 4+2n=7 | | 2(x-2)-3(2x-5)=3x+7 | | 6x-9-8x=9-x+3 | | 5x-8+3x+4=x+7 | | 3(x-2)=5(x+3) | | 8(3*1.6-5)= | | 8(3a-5)= | | 3x-5=5x+3 | | 3x-5=6x+3 | | (a-11)(a+11)= | | 8(x+8)=64 |